2017
DOI: 10.15547/bjvm.950
|View full text |Cite
|
Sign up to set email alerts
|

Allometric analysis of the pharmacokinetics of four cephalosporin antibiotics in mammals

Abstract: SummaryLashev, L., 2017. Allometric analysis of the pharmacokinetics of four cephalosporin antibiotics in mammals. Bulg. J. Vet. Med., 20, No 1,[27][28][29][30][31][32][33][34][35][36][37] Allometric analysis of the total body clearance (Cl B ), steady-state volume of distribution (V ss ) and elimination half-life (t 1/2 ) was performed for cephalexin, cefepime, cefquinone and ceftriaxone based on literature data in mammalian species. Values of Cl B and V ss show allometric dependence on body weight, while va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 50 publications
0
2
0
Order By: Relevance
“…The volume of distribution (Vd/F) is another primary pharmacokinetic parameter, it describes how the molecules of the drug are distributed on the available anatomical spaces of the body (SMITH et al 2015); we found that the Vd/F for oral administration of Norfloxacin was large, and finding is empowered by other studies that denoted to the large volume of distribution of Norfloxacin in different bird species (HARITOVA & LASHEV 2009), such large Vd/F will ensure more accessibility to different anatomical spaces including the intracellular compartment which considered a preferred choice against Norfloxacin sensitive bacteria (CHIFIRIUC et al 2016).…”
Section: Discussionmentioning
confidence: 63%
See 1 more Smart Citation
“…The volume of distribution (Vd/F) is another primary pharmacokinetic parameter, it describes how the molecules of the drug are distributed on the available anatomical spaces of the body (SMITH et al 2015); we found that the Vd/F for oral administration of Norfloxacin was large, and finding is empowered by other studies that denoted to the large volume of distribution of Norfloxacin in different bird species (HARITOVA & LASHEV 2009), such large Vd/F will ensure more accessibility to different anatomical spaces including the intracellular compartment which considered a preferred choice against Norfloxacin sensitive bacteria (CHIFIRIUC et al 2016).…”
Section: Discussionmentioning
confidence: 63%
“…The half-life (t1/2β) was found to be longer than the average in other species, and this finding is a reflection of the large Vd/F, also it could be attributed to some metabolic variations among birds. such long t1/2β may cooperate in increments of the duration of action, consequently increasing of reliability of Norfloxacin against complicated tissue-based infections (SMITH et al 2015, HARITOVA & LASHEV 2009.…”
Section: Discussionmentioning
confidence: 99%